ANALISIS YURIDIS ATAS TUKAR GULING (RUILSLAG) ANTARA TANAH ASET MILIK KODAM I/BUKIT BARISAN DENGAN PT CITRA AGUNG SEJAHTERA DAN PT GLOBALINDO ANUGERAH LESTARI - SLAMET RIYADI (PREMISE LAW JURNAL, 2016)
DOSEN PEMBIMBING:1. Muhd Yamin 2. Syafruddin Kalo 3. T Keizerina Devi A Land and building exchanging or swap owned by the State (ruilslag) is one of the alternatives made by the government agency; in this case, Kodam I/Bukit Barisan, in order to meet the needs of unit facilities in which the asset of Kodam I/Bukit Barisan is part of the State’s property so that the swap should be based on the Directive of the Finance Minister No. 96/PMK.06/2007 on the Procedure of the Implementation of using, utilizing, eliminating, and transferring State-owned property which regulates the procedure of swap (ruilslag). BMN (State-owned property) can be conducted when; a. State-owned property like land and/or building is not in accordance with territorial and urban layout b. State-owned property is not used optimallyc. Scattered State-owned properties are assembledd. Implementation of the government/State strategic plan, ore. State-owned property besides land and/or building which is technologically left behind according to the need/condition/legal provisions Keywords : Swap (ruilslag), Kodam I/Bukit Barisan